2012
DOI: 10.2478/v10011-012-0005-2
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Telomere Shortening and Ageing During Occupational Exposure

Abstract: Summary: Telomere length is considered as a biomarker of ageing, resulting in shortening during the process. The present investigation was an attempt to determine the relative telomere length in mechanical workshop workers. Telomere length shortening in cells during occupational expo sure causes accelerated ageing. Genomic DNA was isolated from buccal epithelial cells collected from 240 individuals, comprising two groups of 120 exposed workers and 120 unexposed controls. Telomere length was measured by using r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…An influence of smoking status on TL within each group was also not found. Eshkoor et al [] observed that smoking affects TL in both workers from mechanical workshops and control groups, while other occupational risk studies have not supported this [Pavanello et al, ]. However, assessment of the entire study population suggested an influence of currently smoking on aTL in our study.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…An influence of smoking status on TL within each group was also not found. Eshkoor et al [] observed that smoking affects TL in both workers from mechanical workshops and control groups, while other occupational risk studies have not supported this [Pavanello et al, ]. However, assessment of the entire study population suggested an influence of currently smoking on aTL in our study.…”
Section: Discussioncontrasting
confidence: 70%
“…Although there are few studies about occupational exposure and effects on TL, there is a growing body of evidence that telomere stability can be affected by occupational and environmental exposures [Eshkoor et al, ]. Both increased and decreased of telomere length have been associated with these exposures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 14 studies, 11 have reported that shorter TL is associated with environmental and occupational exposures, including traffic-related air pollution (ie, particulate matter (PM),7 black carbon (BC),8 and benzene and toluene9), occupational exposure (ie, polycyclic aromatic hydrocarbons (PAHs),10 11 N-nitrosamines,12 pesticides,13 14 lead,15 exposure in car mechanical workshops)16 and hazardous waste 17. Taken together, these studies suggest that exposure to environmental and occupational chemicals may accelerate telomere shortening, which may be a possible biological mechanism for chronic diseases.…”
Section: Tl and Exposure To Environmental And Occupational Chemicalsmentioning
confidence: 99%